THE FEMINICIDE FROM THE POSITIVE SCHOOL - Gabriela Noemí Becerra Ponce (2020)
In this article we will study feminicide from positive school. To do this, we will begin with a brief description of each penal school such as the classical, the eclectic and the positive, and then develop with greater breadth each postulate of the positive school focusing on feminicide, a crime that every day increases in our Peruvian society. According to the postulates of the positive school we have the following objectives: To analyze if the study of the offender is sufficient for the prevention advocated by this school, to determine if the free will influences the behavior of the offender and to analyze whether the penalty works as a prevention of femicide.